Analisis Nilai Ekonomi Obyek Wisata Alam di Kabupaten Samosir, Provinsi Sumatera Utara (Studi Kasus Pemandian Air Panas di Kelurahan Siogung-ogung, Kecamatan Pangururan) - Efrida Tambunan; Siti Latifah; Pindi Patana (Program studi Kehutanan USU, 2013)
The objective of this study is to account the economic value of Hot Spring Nature Tourism Object at Siogung-ogung Village, Samosir Regency with using the travel cost and willingness to pay method. The economic value of Hot Spring Nature Tourism Object, Siogung-ogung Village, Samosir Regency by using the travel cost method is Rp 11.108.505.560/year and willingness to pay method existing conditions Rp 1.000,- until Rp 5.000,- and willingnessto pay with addition facility and management with around Rp 15.000,- until Rp 11.000,-. Keywords: Economic Value, Travel Cost Method, Willingness to Pay, Natural Hot Spring.